Incorporating fast charging stations accessibility into an urban traffic assignment model based on the Frank – Wolfe algorithm - Sizhuo, Du; Sarazhinsky, Denis S.; Kapski, Denis V. (Journal of the Belarusian State University. Mathematics and Informatics, 2026)
The growing use of electric vehicles necessitates the adaptation of transport models to account for the specifics of their operation. The aim of this work is to modify the classic traffic assignment model based on the Frank – Wolfe algorithm, widely used in transportation planning, to accurately reflect electric vehicle charging processes in urban environments. The novelty of the research lies in the development of an approach that, unlike existing approaches, comprehensively addresses three key features: the requirement for an electric vehicle needing to charge to route through exactly one charging station; the possibility of routing along paths with cycles to access charging stations and subsequently reach the destination, considering urban road network constraints; the behavioural aspect of a user’s decision to forgo charging if the total time costs (including travel to the station and queuing) exceed a certain threshold. The paper also proposes a time-cost function that accounts for the specifics of the charging process, including queues and the number of charging spots. The results demonstrate that the classic traffic assignment model based on the Frank – Wolfe algorithm can indeed be modified to incorporate these features. It is noted that the proposed model may exhibit multiple equilibrium flow distributions, dependent on initial conditions. The practical significance of the work lies in its potential for more accurate modelling of traffic flows and the load on urban charging infrastructure.
Keywords: electric vehicle; fast charging station; traffic assignment; Wardrop equilibrium; Frank – Wolfe algorithm